2022
DOI: 10.3389/fcell.2022.935023
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 represents a new target to boost Ibrutinib and Venetoclax induced cytotoxicity in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an incurable B cell non-Hodgkin lymphoma, characterized by frequent relapses. In the last decade, the pro-survival pathways related to BCR signaling and Bcl-2 have been considered rational therapeutic targets in B cell derived lymphomas. The BTK inhibitor Ibrutinib and the Bcl-2 inhibitor Venetoclax are emerging as effective drugs for MCL. However, primary and acquired resistance also to these agents may occur. Protein Kinase CK2 is a S/T kinase overexpressed in many solid and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…These latter are required for substrate recruitment and kinase activity modulation (10). CK2 has been found overexpressed in a wide array of solid and hematologic tumors (11-15) and shown to sustain survival and proliferation of malignant B cells in chronic lymphocytic leukemia, multiple myeloma, mantle cell lymphoma, B-acute lymphoblastic leukemia and diffuse large B cell lymphoma (DLBCL) (13,(16)(17)(18)(19)(20)(21)(22). Multiple proteins taking part in hemo-lymphopoiesis are CK2 substrates, however, the physiological role of this kinase in B cell biology has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…These latter are required for substrate recruitment and kinase activity modulation (10). CK2 has been found overexpressed in a wide array of solid and hematologic tumors (11-15) and shown to sustain survival and proliferation of malignant B cells in chronic lymphocytic leukemia, multiple myeloma, mantle cell lymphoma, B-acute lymphoblastic leukemia and diffuse large B cell lymphoma (DLBCL) (13,(16)(17)(18)(19)(20)(21)(22). Multiple proteins taking part in hemo-lymphopoiesis are CK2 substrates, however, the physiological role of this kinase in B cell biology has been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have provided strong evidence that, in accordance with the paradigm known as “non-oncogene dependence” ( 18 , 42 ), overexpression of CK2α is believed to be responsible for pivotal mechanisms of cell proliferation and survival also in cHL.…”
Section: Discussionmentioning
confidence: 64%
“…Previously, we and other groups demonstrated that both CK2α and CK2β were overexpressed and essential for neoplastic cell growth. Inhibition of CK2 triggered apoptosis in neoplastic cells of multiple myeloma ( 30 ), acute leukemias ( 26 ), and non-Hodgkin lymphomas ( 18 , 25 ), without a significant impact on normal lymphocytes ( 31 ). However, the role of CK2 in cHL is unknown and has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations